Who Governs at What Price? Technocratic Dominance, Ways of Knowing, and Long-Term Resilience of Brazil's Water System - Almazán-Casali, Stefania; Puga, Bruno Peregrina; Lemos, Maria Carmen (Frontiers in Water, 2021)
Technocratic decision making has been long criticized for dampening participation and limiting the range of adaptive choices through its overreliance on infrastructure-based solutions. There has been growing attention to how technocratic approaches shape long-term resilience of water systems, especially under the threat of climatic change impacts. In Brazil, even under its highly decentralized and participatory water management system, technical expertise and science-based decisions have been often promoted as a desirable mechanism to insulate governance outcomes from the country’s prevailing clientelistic and rent-seeking politics. Yet, Brazilian river basins continue to struggle with long-standing problems (such as universal access to sanitation) and increasing challenges for guaranteeing water provision under recurrent drought. In this study, we examine how technocratic insulation, different ways of knowing, (WoKs), and participatory governance shape long-term resilience in one of Brazil’s most important river basins, the Piracicaba-Capivari-Jundiai (PCJ). By taking an in-depth look at how the PCJ River Basin’s governance system responded to the 2014 Brazilian water crisis, we seek to understand how planning decisions in the aftermath of the crisis were influenced by different actors, and how the outcomes of those decisions are likely to shape long term resilience. Based on 27 in-depth interviews with members of the PCJ River Basin Committees, we show how a distinct preference for infrastructure-based solutions to deal with on-going and upcoming challenges may be unsustainable under climate change as the basin’s traditional technocratic approach failed both to insulate its decisions from politics and to explore adaptive water management solutions that might be key to shape long-term resilience.